2013
DOI: 10.7166/24-2-749
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Lean Manufacturing Audits in Measuring Operational Performance Improvements

Abstract: The hypothesis that lean manufacturing audits are an effective way to measure improvements in operational performance was tested using 64 manufacturing sites owned by a FTSE 100 company. Commonly-used lean characteristics were evaluated: policy deployment, standardised work, visual management and housekeeping, quick changeover techniques, total productive maintenance, continuous improvement (kaizen), error proofing, cultural awareness, material control, and levelling (heijunka). Operational performance was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
(6 reference statements)
0
13
0
2
Order By: Relevance
“…Lean Production Framework Kurdve et al (2011) dealt with the environmental value stream mapping for achieving better results in two case studies at Volvo; Nasab et al (2013) introduced an integrated dynamic approach to investigate the technology effectiveness of lean manufacturing in enterprises and ability to alter the parameter's affects on others; Venkataramana et al (2014) aimed at lean implementation in an Indian automotive industry through multi-criteria decision making model & analytical hierarchy process to create product mix flexibility; Marudhamuthu et al (2011) addressed the lean implementation in an Indian garment export industry by VSM and single minute exchange of die (SMED) approaches which resulted in reduced set up time; Mittal and Sangwan (2014) developed a model for environmentally conscious manufacturing by SPSS tool, exploratory & confirmatory factor analysis and SEM to validate the model; Taggart and Kienhöfer (2013) concluded that lean audits are only effective ways to measure improvements in operational performance and tested it in 64 manufacturing sites; Sullivan et al (2002) provided a roadmap for the analysis of equipment replacement decision problems through VSM; Wang et al (2008) introduced a step-by-step implementation framework for lean production & product development by means of marketing research on product development & design processes (Figure 7); Upadhye et al (2014) tried to find out the implementation enablers of lean tools i.e. Just-in-Time in the Indian corrugated packaging industry through interpretive structural modeling; Jaganathan (2014) carried out the assembly line balancing & layout modification in a garment industry using largest candidate algorithm rule, and increased the efficiency up to 26% & the productivity by 25%.…”
Section: Figurementioning
confidence: 99%
“…Lean Production Framework Kurdve et al (2011) dealt with the environmental value stream mapping for achieving better results in two case studies at Volvo; Nasab et al (2013) introduced an integrated dynamic approach to investigate the technology effectiveness of lean manufacturing in enterprises and ability to alter the parameter's affects on others; Venkataramana et al (2014) aimed at lean implementation in an Indian automotive industry through multi-criteria decision making model & analytical hierarchy process to create product mix flexibility; Marudhamuthu et al (2011) addressed the lean implementation in an Indian garment export industry by VSM and single minute exchange of die (SMED) approaches which resulted in reduced set up time; Mittal and Sangwan (2014) developed a model for environmentally conscious manufacturing by SPSS tool, exploratory & confirmatory factor analysis and SEM to validate the model; Taggart and Kienhöfer (2013) concluded that lean audits are only effective ways to measure improvements in operational performance and tested it in 64 manufacturing sites; Sullivan et al (2002) provided a roadmap for the analysis of equipment replacement decision problems through VSM; Wang et al (2008) introduced a step-by-step implementation framework for lean production & product development by means of marketing research on product development & design processes (Figure 7); Upadhye et al (2014) tried to find out the implementation enablers of lean tools i.e. Just-in-Time in the Indian corrugated packaging industry through interpretive structural modeling; Jaganathan (2014) carried out the assembly line balancing & layout modification in a garment industry using largest candidate algorithm rule, and increased the efficiency up to 26% & the productivity by 25%.…”
Section: Figurementioning
confidence: 99%
“…The companies seek to find methodologies that allow them to respond to the growing challenges that are currently posed to them, and the Lean Manufacturing philosophy [1,2,8,13,15,16] and some other more or less closely related subjects are often the solution found to solve their problems [5][6][7]9,11,14,15,17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The goal of Lean Manufacturing is to minimize any kind of waste, which becomes a progressively more complex goal to achieve, to make each company more competitive in the current global market context [13,15,16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Aburas [1] recognises that evaluating the corporate performance of a multi-business company is complicated because it should be viewed from various perspectives and has to satisfy multiple objectives. Taggart and Kienhöfer [34] propose that some commonly-used operational performance measures are on-time-delivery, inventory turns, and direct labour use. Besides, the simulation modelling is applied to investigate the concept of performance analysis [18].…”
Section: Introductionmentioning
confidence: 99%